KEBIJAKAN PENGEMBANGAN PERGURUAN TINGGI DAN AKTUALISASI PERANNYA DALAM PEMERINTAHAN DAN PEMBANGUNAN - Tatang Sudrajat (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2012)
The existency of college in the country is very strategic. College has provided contributive role to the development andÂ  sustainable government. The future generation will be born from there. The generation which is capable of moving wheels of government and development. Therefore, policy for development will be very important, besides the consistency of policy implementation and continuous evaluation.